Advances in structural design of lipid-based nanoparticle carriers for delivery of macromolecular drugs, phytochemicals and anti-tumor agents - Angelova, Angelina; Garamus, Vasil M; Angelov, Borislav; Tian, Zhenfen; Li, Yawen; Zou, Aihua (Advances in colloid and interface science, 2017)
The present work highlights recent achievements in development of nanostructured dispersions and biocolloids for drug delivery applications. We emphasize the key role of biological small-angle X-ray scattering (BioSAXS) investigations for the nanomedicine design. A focus is given on controlled encapsulation of small molecular weight phytochemical drugs in lipid-based nanocarriers as well as on encapsulation of macromolecular siRNA, plasmid DNA, peptide and protein pharmaceuticals in nanostructured nanoparticles that may provide efficient intracellular delivery and triggered drug release. Selected examples of utilisation of the BioSAXS method for characterization of various types of liquid crystalline nanoorganizations (liposome, spongosome, cubosome, hexosome, and nanostructured lipid carriers) are discussed in view of the successful encapsulation and protection of phytochemicals and therapeutic biomolecules in the hydrophobic or the hydrophilic compartments of the nanocarriers. We conclude that the structural design of the nanoparticulate carriers is of crucial importance for the therapeutic outcome and the triggered drug release from biocolloids.
Keywords: Nanoparticles; Humans; Hydrophobic and Hydrophilic Interactions; Drug Carriers; Nanostructured lipid carriers; Liquid crystalline nanocarriers; Antineoplastic Agents; Nanomedicines; BioSAXS; lidé; plazmidy; fytonutrienty; Drug Liberation; peptidy; uvolňování léčiv; Peptides; RNA, Small Interfering; malá interferující RNA; Phytochemicals; difrakce rentgenového záření; X-Ray Diffraction; Self-assembled biomaterials; Drug Compounding; nanočástice; nosiče léků; Scattering, Small Angle; příprava léků; Colloids; protinádorové látky; Drug delivery; maloúhlový rozptyl; Plasmids; hydrofobní a hydrofilní interakce; koloidy